Hubungan Panjang Berat, Faktor Kondisi, dan Komposisi Makanan Ikan Saluang (Rasbora argyrotaenia Blkr) di Dataran Banjir Sungai Rungan, Kalimantan Tengah - Bambang Sulistiyarto (Fakultas Peternakan Universitas Kristen Palangka Raya, 2012)
The study aims were to evaluate length-weight relationship (LWR), condition factor, and diet composition of saluang fish (Rasbora argyrotaenia Blkr) in Rungan River Floodplain at dry season and rainy season. This study showed that the coefficient b of the LWR < 3, indicated saluang fish have negative allometric growth. Coefficient b at dry season (1,48) less then at rainy season (b = 2,63), indicated fish grow faster at rainy season. The mean value of condition factor (K) were 1,2776 ± 0,1903 at dry season and 1,1775 ± 0,1077 at rainy season. The mean relative condition factor (Kr) at both season were close to 100, indicated fish was in good condition at both season. Season shift was effect to consumption level of food materials.